Solution NMR characterization of apical membrane antigen 1 and small molecule interactions as a basis for designing new antimalarials. Issue 6 (24th January 2016) - Krishnarjuna, Bankala; Lim, San Sui; Devine, Shane M.; Debono, Cael O.; Lam, Raymond; Chandrashekaran, Indu R.; Jaipuria, Garima; Yagi, Hiromasa; Atreya, Hanudatta S.; Scanlon, Martin J.; MacRaild, Christopher A.; Scammells, Peter J.; et al.
Abstract : Plasmodium falciparum apical membrane antigen 1 ( Pf AMA1) plays an important role in the invasion by merozoites of human red blood cells during a malaria infection. A key region of Pf AMA1 is a conserved hydrophobic cleft formed by 12 hydrophobic residues. As anti‐apical membrane antigen 1 antibodies and other inhibitory molecules that target this hydrophobic cleft are able to block the invasion process, Pf AMA1 is an attractive target for the development of strain‐transcending antimalarial agents. As solution nuclear magnetic resonance spectroscopy is a valuable technique for the rapid characterization of protein–ligand interactions, we have determined the sequence‐specific backbone assignments for Pf AMA1 from two P. falciparum strains, FVO and 3D7. Both selective labelling and unlabelling strategies were used to complement triple‐resonance experiments in order to facilitate the assignment process. We have then used these assignments for mapping the binding sites for small molecules, including benzimidazoles, pyrazoles and 2‐aminothiazoles, which were selected on the basis of their affinities measured from surface plasmon resonance binding experiments. Among the compounds tested, benzimidazoles showed binding to a similar region on both FVO and 3D7 Pf AMA1, suggesting that these compounds are promising scaffolds for the development of novel Pf AMA1 inhibitors. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Backbone resonance assignments for apical membrane antigen 1 (AMA1) (DI + DII) from FVO and 3D7 strains of Plasmodium falciparum were determined using triple‐resonance nuclear magnetic resonance experiments together with different isotope labelling methods. Two‐dimensional [ 1 H‐ 15 N]‐transverse relaxation optimized spectroscopy experiments were used to map the binding sites for small molecules, including benzimidazoles, pyrazoles and 2‐aminothiazoles, which were selected from surface plasmon resonance binding experiments based on their affinities for AMA1. Our results suggest that benzimidazoles bind to a similar region on both FVO and 3D7 P. falciparum AMA1 and, thus, that they are promising scaffolds for the development of new P. falciparum AMA1 inhibitors.